Um ambiente online para apoio dialogado à aprendizagem de programação - Santos, Renato de Moura (2019)
Teaching the discipline of algorithms and programming language has become increasingly important in a world connected by information technology, and learning is essential for the other disciplines in a computer course, as algorithmic problem solving occurs. practically the entire course. Although the importance of programming teaching, the learning difficulties of this subject are notorious and the teaching process presents several challenges to the teacher and the student. The main difficulties of the students are evidenced during the accomplishment of the proposed activities and lie mainly in the development of the programming logic, lack of mastery of the programming language syntax and semantics and difficulties in the interpretation of the proposed problems. On the other hand, teaching programming for beginning students requires a strong demand for interaction from the teacher to attend, monitor, mediate and evaluate these students. This paper presents a programming environment that supports conversation with the student and aims to provide the conditions for this student to obtain feedback during the resolution of the proposed problems while freeing the teacher from the recurring demands of attendance. Therefore, a case study and theoretical reference research were conducted to know the recurrent difficulties that could be transferred to the environment and to identify the computational approaches that could be used in the implementation of an environment proposal. Intelligent agent-based pedagogical assistants were created responsible for attending to the difficulties reported by the students or dedicated to the analysis of the source code of the developed activities in search of signs of difficulties not directly expressed. The validation of the proposal occurs with the implementation of a proof of concept of part of the solution and the application of this prototype to an intensive course of introduction to the programming language. The collected data were analyzed and the obtained results showed pieces of evidence that the proposed solution provides the conditions to improve the support to the student during the accomplishment of the activities, besides releasing the teacher of the recurrent cases of the requests of attendance.